PENGANGGURAN DAN POTENSI EKONOMI KREATIVE MADURA - Akh. Fawaid; Ahmad Rajaul Masrur; USWATUN HASANAH (STIE Bakti Bangsa Pamekasan, 2021)
Suramadu Bridge which stretches and brings Madura and Surabaya together, has not yet been able to absorb unemployment in Madura. The proof, the number of unemployment found in four districts in Madura, is still very high. While on the other hand, Madura has quite a lot of creative economic potential. Both culinary, work and cultural arts that have the potential to be sold. This research uses descriptive qualitative method. This method is used, to fully understand the problem of high unemployment and creative economic potential that can be developed to address the high unemployment solution in Madura. The data source is free directional interview. Which is reinforced by some existing literature.